THE IMPACT OF FLEXIBLE WORK ARRANGEMENTS AND JOB AUTONOMY ON WORK PERFORMANCE THROUGH WORK ENGAGEMENT AS A MEDIATING VARIABLE AT PT PABRIK KERTAS TJIWI KIMIA, TBK - Yohanes Wibisono; Budi Eko Soetjipto; Sopiah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the impact of flexible work arrangements (FWA) and job autonomy (JA) on job performance (JP), examining work engagement (WE) as a mediating variable. The research was conducted among permanent production employees at PT Pabrik Kertas Tjiwi Kimia, Tbk in Indonesia, using a quantitative approach with an explanatory design. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that JA has a positive and significant influence on JP, both directly and indirectly through WE. However, FWA does not have a significant direct influence on JP but indirectly affects JP through WE. These findings highlight the importance of JA in enhancing intrinsic motivation and performance, as well as the role of WE in connecting job resources with performance outcomes. The study emphasizes the need to balance flexibility with structure in job design to optimize employee engagement and performance in a manufacturing environment.